Numerical Evaluations of Diffraction Formulas for the Canonical Wedge-Scattering Problem - Hacivelioglu, Feray; Sevgi, Levent; Ufimtsev, Pyotr Ya. (IEEE-Inst Electrical Electronics Engineers Inc, 2013)
Numerical computations of different diffraction representations for the canonical wedge-scattering problem are discussed. Representations include total-field exact series summation, exact diffraction integral, and the Physical Optics (PO), Physical Theory of Diffraction (PTD), and Parabolic Equation (PE) techniques, and the Uniform Theory of Diffraction (UTD). Numerical challenges and advantages of each are given.
Keywords: Wedge scattering; line source; reflected field; diffracted field; cylindrical wave; plane wave; exact series; exact Integrals; high frequency asymptotics; parabolic equation; PO; PTD; UTD; numerical integration; Fresnel integral